2021
DOI: 10.3389/fpls.2021.651716
|View full text |Cite
|
Sign up to set email alerts
|

Disarming the Host: Detoxification of Plant Defense Compounds During Fungal Necrotrophy

Abstract: While fungal biotrophs are dependent on successfully suppressing/subverting host defenses during their interaction with live cells, necrotrophs, due to their lifestyle are often confronted with a suite of toxic metabolites. These include an assortment of plant defense compounds (PDCs) which can demonstrate broad antifungal activity. These PDCs can be either constitutively present in plant tissue or induced in response to infection, but are nevertheless an important obstacle which needs to be overcome for succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 146 publications
0
45
0
Order By: Relevance
“…Our data revealed that Khib is involved not only in the basic life functions of A. niger but also in its pathogenic process. As with any other fungus, A. niger must degrade the cell wall and overcome plant defense compounds, which have broad antimicrobial properties, in order to successfully infect and colonize a host ( Westrick et al, 2021 ), our research showed that some 2-hydroxyisobutyrylated proteins are associated with polygalacturonase activity and glycoside hydrolases, they usually have more than one Khib sites ( Figure 6 ). These proteins are responsible for fungal decomposition of pectin in plant cell walls and provide the carbon sources for fungal growth ( Have et al, 2003 ; Reignault et al, 2008 ).…”
Section: Discussionmentioning
confidence: 87%
“…Our data revealed that Khib is involved not only in the basic life functions of A. niger but also in its pathogenic process. As with any other fungus, A. niger must degrade the cell wall and overcome plant defense compounds, which have broad antimicrobial properties, in order to successfully infect and colonize a host ( Westrick et al, 2021 ), our research showed that some 2-hydroxyisobutyrylated proteins are associated with polygalacturonase activity and glycoside hydrolases, they usually have more than one Khib sites ( Figure 6 ). These proteins are responsible for fungal decomposition of pectin in plant cell walls and provide the carbon sources for fungal growth ( Have et al, 2003 ; Reignault et al, 2008 ).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, seven genes encoding secreted proteins present only in D. caulivora and not in other Diaporthe species were upregulated, including a kievitone hydratase and six hypothetical proteins, three of which are D. caulivora -specific with no hit in public databases. Interestingly, kievitone hydratases are involved in detoxification processes of the phenylpropanoid kievitone, which play an important role in legumes defense against pathogen attack [ 53 ]. Of the total number of D. caulivora effectors, 23.3% (31 genes) were upregulated, including those encoding several CAZymes, a cell wall glycoprotein, several small secreted proteins, and hypothetical proteins (Additional files 12 and 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Inducing cell death in plants can release many plant-derived compounds that are toxic to fungi, so it is also important to consider fungal proteins involved in tolerating this environment. These detoxification mechanisms were the subject of another recent review on necrotrophic fungi (Westrick et al, 2021), and will not be covered here.…”
Section: Plant Cell Death-inducing Effectorsmentioning
confidence: 99%